2012
DOI: 10.1007/s00405-012-1990-y
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life after tonsillotomy versus tonsillectomy in young adults: 6 years postsurgery follow-up

Abstract: Introduction:The indication for tonsil surgery is tonsillitis or obstructive symptoms due to tonsillar

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 30 publications
2
26
0
Order By: Relevance
“…However, the study of Ericsson and Hultcrantz [6] supports our findings. Good short-and long-term patient satisfaction after TO procedures is already demonstrated by Krespi et al [13,14] and Wireklint and Ericsson [15], and these findings are consistent with this study's findings regarding patients prompt resumption of daily activities and self-reported overall high satisfaction. It is surprising though that, after 1-year follow-up, patients were equally satisfied.…”
Section: Discussionsupporting
confidence: 92%
“…However, the study of Ericsson and Hultcrantz [6] supports our findings. Good short-and long-term patient satisfaction after TO procedures is already demonstrated by Krespi et al [13,14] and Wireklint and Ericsson [15], and these findings are consistent with this study's findings regarding patients prompt resumption of daily activities and self-reported overall high satisfaction. It is surprising though that, after 1-year follow-up, patients were equally satisfied.…”
Section: Discussionsupporting
confidence: 92%
“…Follow-up was 1 day in the study by Arya et al [10], 14 d in the study by Hall et al [11], 6 months in the study by Bender et al [13], 1 year in the study by Lourijssen et al [4] and 12 to 24 months in the study by Nemati et al [14] and 32 months in the study by Johnston et al [12]. In the consecutive papers on the Swedish cohort, follow-up was 3 weeks, 1 and 6 years [7][8][9].…”
Section: Follow-upmentioning
confidence: 97%
“…The papers by Ericsson and Hultcrantz [7], Ericsson and Ledin [8] and Wireklint and Ericsson [9] reported on the same cohort of patients in Link€ oping, Sweden, using a consecutively longer follow-up period. From here on, we will refer to this cohort as 'the Swedish cohort'.…”
Section: Literature Searchmentioning
confidence: 99%
See 2 more Smart Citations